Analisis Perbandingan Sensor Suhu dan Kelembaban DHT-11 DAN AHT-10 Dengan Perangkat Lutron AM4205A - Hanes, Natanael Michael; Wahab, Wahidin; Setyaningsih, Endah (Fakultas Teknik dan Informatika Universitas Panca Marga, 2024)
Temperature and humidity sensors are key components in various systems related to environmental monitoring, process control, and product safety. Accurate measurement of temperature and humidity is crucial for maintaining product quality, ensuring operational safety, and minimizing the risk of equipment damage or failure. However, temperature and humidity sensors require regular calibration to ensure measurement consistency and accuracy. Without proper calibration, these sensors are prone to drift or changes in measurement characteristics over time, environment, and usage, which can lead to significant measurement errors and negatively impact product quality, operational safety, and process efficiency. This study aims to develop expertise in programming and calibrating temperature and humidity sensors for field applications. The primary focus is to compare the performance of the DHT11 and AHT10 sensors using the Lutron AM4205A device as a reference measurement. The results of this study are expected to provide insights into the reliability and accuracy of these sensors.